Experimental investigation on fresh water production using air gap membrane distillation - Roslan, Muhamad Hafizuddin; Bahar, Rubina; Hilmy, Irfan (Science Publishing Corporation, RAK Free Trade Zone, 2019)
Fresh waters are one of essential element to human being. Since five years ago, certain area in Selangor, Malaysia, facing insufficient water supply due to the lack of fresh water resources and the increase of maintenances cost. To overcome this problem, other alternatives in producing fresh water should be implemented. As a suggestion, freshwater production using membrane distillation could be utilized. Membrane distillation with solar heat as a main power source is a good solution for this problem. This mechanism not only could help in producing enough fresh water supplies, but also could help reducing the use of non-renewable energy. Heating mechanism using solar panel was utilized. However, to use this mechanism, study about the way to confine the heat, and the mechanism compatibility should be done first. To achieve those requirements, the overall system of fresh water production should be evaluated first. The performance of the current system has been evaluated. From the result, it can be seen the potential and feasibility of this system to produce the fresh water.